Détermination De La Dose Optimale D’engrais Minéral 15-15-15 Sur Cinq (05) Variétés De Maïs Doux (Zea Mays L. ssp. saccharata) Au Sénégal - Diallo, Mariama Dalanda; Toure, Aïchatou; Mbacke, Fatou Diop; Saleh, Minda Mahamat; Touroumgaye, Goalbaye; Ndiaye, Ahmadou Bamba; Ndiaye, Nafi Diop; Diop, Aliou; Guisse, Aliou (European Scientific Journal, ESJ, 2016)
The objective of this study is to assess the response of five varieties of sweet maize namely, Prime plus (V1), Shy 1036 (V2), Colombus (V3), GSS (V4), and JKMH-45 (V5) to three different doses of NPK (15-15-15) fertilizer: F1 (normal dose), F2 (75% of the normal dose) and F3 (125% of the normal dose). An experimental design in Fisher blocs with 15 treatments was established at the ISRA/CRA experimental station in Saint Louis (Senegal). The results have shown that 30 days after sowing (DAS), the varieties Colombus, GSS and JKMH-45 have had the highest heights with 32.75 cm, 31.85 cm and 31.46 cm, respectively with the F2 dose. The variety JKMH-45 has a greater height of the upper ear (89.39 cm) at 60 DAS and valorizes better the F2 dose (75% of the normal dose). The F3 dose increases less the plant’s height. A non-significant difference was observed among the 5 varieties used regarding the precocity. The variety V2 or Shy 1036 developed ears at first, but is not precocious compared to the variety V1 that not only shows earlier anthesis but also an appearance of darker hairs. The variety JKMH-45, although presenting darker hairs after the variety Prime plus, is the latest variety, earing at 57 DAS and with male and female anthesis appearing at 59 DAS and 63 DAS. This study can constitute a basic criterion in differentiating the sweet maize varieties in Senegal. It would also allow more financial saving on inputs and contribute to the maximization ofproduction if the choice of the variety is well done.